Response of VO2max to dark chocolate consumption in healthy subjects: A systematic review and meta‐analysis of randomized controlled trials - Aref Mehdipour; Saber Saedmocheshi; Giuseppe Potrick Stefani; Ehsan Amiri; Diako Heidary (Physiological Reports)
Abstract The potential role of dark chocolate (DC) in enhancing exercise performance remains underexplored. While DC has been associated with various health benefits, its specific impact on endurance performance, particularly VO2max, has not been conclusively established. This meta‐analysis examined the effect of DC on VO2max in healthy individuals using PRISMA guidelines. Following the application of inclusion and exclusion criteria, five randomized controlled trials (RCTs) involving 144 participants were included, with VO2max as the primary outcome. The meta‐analysis revealed no significant effect of DC on VO2max (SMD = 0.14, 95% CI: −0.16 to 0.44, p = 0.36). Heterogeneity among the studies was low (Q‐value = 3.34, I2 = 0.00, p = 0.50), and sensitivity analysis confirmed the robustness of the findings, as excluding individual studies did not alter the results (SMD = 0.14, 95% CI: −0.16 to 0.44, p = 0.36). In conclusion, this meta‐analysis suggests that DC consumption does not significantly improve VO2max in healthy individuals. Future research should explore the effects of DC on other aspects of exercise performance, as well as its long‐term impact, to better understand its potential role in athletic and health‐related outcomes.